An Exploration of Dialogue to Promote Assessment Feedback Literacy (Teaching and Learning Inquiry, 2024)
This study explores the challenges of assessment feedback in a business school in the UK. Like many business schools, it operates at volume with large class sizes and an internationally diverse student cohort. To operate effectively, it has adopted a bureaucratic administrative approach to assessment in order to address concerns over timeliness, consistency, and quality of feedback. Drawing on socio-constructivist and sociocultural perspectives, this study explores the role of dialogue and reciprocity in the assessment feedback process with a focus on grade descriptors and their role in fostering student success in their learning. Through an action research approach with a cohort of students on a three-year module, the study examines how grade descriptors are experienced by students and student perceptions of their purpose and function within the higher educational organisational context and the positioning of tutor and student in the assessment process. The findings suggest a desire amongst students for a more collaborative learning approach and the benefits for students of doing so. The paper concludes with discussion of the implications of adopting a more dialogic approach to assessment feedback for students, tutors, and universities.Read the corresponding ISSOTL blog post here.